Secretory structures of the Adesmia clade (Leguminosae): Implications for evolutionary adaptation in dry environments - Fortuna-Perez, Ana Paula [UNESP]; Marinho, Cristina Ribeiro; Vatanparast, Mohammad; Vargas, Wanderleia de [UNESP]; Iganci, Joao Ricardo Vieira; Lewis, Gwilym Peter; Candido, Elisa Silva; Moura, Tania Maria de; Monteir, Thiago Cobra e [UNESP]; Miotto, Silvia Teresinha Sfoggia; Teixeira, Simone Padua (Elsevier B.V., 2021)
The Dalbergioid Adesmia Glade comprises Adesmia DC., Amicia Kunth, Nissolia Jacq., Poiretia Vent., and Zornia J. F. Gmel., all predominantly South American genera except for Zornia which has a pantmpical distribution. These taxa share a shrubby or herbaceous habit with glands present on some part of the plant (e.g., stems, leaflets). However, the evolutionary relationships of the full range of secretory structures observed in previous studies are not fully understood. Thus, the goal of this study is to characterize and compare the occurrence and morphology of these glands in leaflets of species of the Adesmia clade. In addition, secretory structures were showed in a phylogenetic context in members of the Adesmia clade. The mature subterminal leaflets of 81 taxa, 79 from the Adesmia clade and two species of the Ptemcarpus clade, were sampled from herbaria and living specimens. All genera of the Adesmia clade shared the presence of secretory, mucilaginous idioblasts in the epidermis of their leaflets. Genera of the clade inhabit dry environments, including open areas and highland grasslands (e.g., Savanna, Patagonian steppe, and the Andes). The presence of mucilage in the epidermis of these genera might be an adaptation to reduce water loss through transpiration, providing a hydrophilic interface between the leaflet surface and the environment, protecting plants from intensive radiation. Phenolic idioblasts were found in the mesophyll of Amicia and Zornia. Secretory cavities were observed in Amicia, Poiretia and Zornia. The occurrence of secretory cavities only in these three phylogenetically closely related genera is considered a synapomorphic character as shown by our character reconstruction analysis. The presence of secretory idioblasts is a unifying characteristic of all genera of the Adesmia clade.
Keywords: Adaptation; Dalbergieae; Fabaceae; Papilionoideae; Secretory cavities; Secretory idioblasts